2012
DOI: 10.1007/s10658-012-9950-3
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring diversity of Erwinia amylovora population in Serbia by conventional and automated techniques and detection of new PFGE patterns

Abstract: Forty Erwinia amylovora strains originating from different host plants and locations in Serbia and one strain from Montenegro were characterized by conventional, automated and molecular techniques. All strains were Gram-negative, nonfluorescent, facultative anaerobes, oxidase negative, levan positive, produced necrotic lesions followed by bacterial exudate on artificially inoculated immature pear fruits and caused HR on tobacco. Based on carbon source utilization, all strains tested with the Biolog system were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
7
1
Order By: Relevance
“…Although all studied strains formed levantype colonies, differences were observed in their size, convexity and edges, which grouped the strains into three types. Similar variations in the shape of colonies were also reported by Momol & Aldwinckle (2000), especially between strains isolated from Maloideae and Rubus spp., and later observed also by Ivanović et al, (2012). The results of our research did not indicate a correlation between the morphology of colonies on KB and NSA media and the pathogenicity of the strains, nor their host species or geographical origin.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Although all studied strains formed levantype colonies, differences were observed in their size, convexity and edges, which grouped the strains into three types. Similar variations in the shape of colonies were also reported by Momol & Aldwinckle (2000), especially between strains isolated from Maloideae and Rubus spp., and later observed also by Ivanović et al, (2012). The results of our research did not indicate a correlation between the morphology of colonies on KB and NSA media and the pathogenicity of the strains, nor their host species or geographical origin.…”
Section: Discussioncontrasting
confidence: 62%
“…The PFGE has been used for differentiation of E. amylovora strains, as well as for monitoring of introductions and spread of the pathogen (Jock et al, 2002;Donat et al, 2007). This method revealed at least two possible directions of E. amylovora introduction into Serbia (Ivanović et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains were isolated from different host plants, at different localities and in different years in Serbia and had various PFGE patterns in their genome, representing distant populations of the pathogen. The strains were previously identified based on biochemical properties, immature pear fruit assay, Biolog TM MicroPlate System and Fatty acid analysis (IVANOVIĆ et al, 2012). Type strain of E. amylovora NCPPB 595 was used as a positive control.…”
Section: Bacterial Strains Growth Conditions and Specificity Of Pcr mentioning
confidence: 99%
“…Recently, in 2012, E. amylovora was reported from different host plants and locations in Serbia and Montenegro (Ivanovic et al, 2012) and it is also present in other countries like Tunisia, first reported in 2014 in pear (Rhouma et al, 2014) or Algeria, that had its first characterization of isolates in 2012 (Laala et al, 2012).…”
Section: Global Distributionmentioning
confidence: 99%